2022
DOI: 10.1021/acsomega.2c04113
|View full text |Cite
|
Sign up to set email alerts
|

Copper Complexes of 1,4-Naphthoquinone Containing Thiosemicarbazide and Triphenylphosphine Oxide Moieties; Synthesis and Identification by NMR, IR, Mass, UV Spectra, and DFT Calculations

Abstract: New 1,4-naphthoquinone derived by triphenylphosphaneylidene (Ph 3 P) and N -substituted-hydrazine-1-carbothioamides were obtained during a one-pot reaction of 2,3-dichloro-1,4-naphthoquinone with thiosemicarbazides, Ph 3 P and in the presence of triethyl amine (Et 3 N) as a catalyst. The structure of the ligands was established by ESI, IR, and NMR spectra, in addition to elemental analyses and X-ray structure analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Thiosemicarbazones derived by 1,4-naphthoquinone 29a – f were established upon mixing equimolar amounts of thiosemicarbazides 11e – j with 2,3-dichloro-1,4-naphthoquinone ( 28 ), Ph 3 P and in the presence of Et 3 N as a catalyst and acetonitrile as a solvent. Triphenylphosphine-ylidene)-3,4-dihydronaphthalen-2(1 H )-ylidene)- N -substituted-hydrazine-1-carbothioamides 29a – f were obtained in 72–82% yield ( Scheme 13 ) [ 63 ].…”
Section: Synthesis Of Thiosemicarbazide Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiosemicarbazones derived by 1,4-naphthoquinone 29a – f were established upon mixing equimolar amounts of thiosemicarbazides 11e – j with 2,3-dichloro-1,4-naphthoquinone ( 28 ), Ph 3 P and in the presence of Et 3 N as a catalyst and acetonitrile as a solvent. Triphenylphosphine-ylidene)-3,4-dihydronaphthalen-2(1 H )-ylidene)- N -substituted-hydrazine-1-carbothioamides 29a – f were obtained in 72–82% yield ( Scheme 13 ) [ 63 ].…”
Section: Synthesis Of Thiosemicarbazide Derivativesmentioning
confidence: 99%
“…Recently Aly et al [ 63 ] reported that the reaction of equal equivalents of compounds 29a – f with Ph 3 P and CuCl 2 .2H 2 O in ethanol at rt and for 1–3 d produced the bidentate Cu-complexes 54a – f in 80–93% yields as indicated in Scheme 26 .…”
Section: Metal Complexes Of Thiosemicarbazones and Thiocarbazonesmentioning
confidence: 99%
“…Despite a fairly large number of methods, problems in determining silver in various objects remain. This is explained, first of all, by increased requirements for the quality of the results of such analyzes, as well as by the complexity of most silver-containing samples [3][4][5]. It is known that in many natural and industrial samples, silver is found in ultra-small quantities against the background of large quantities of copper, nickel, cobalt, iron, cadmium and others that are quite similar in chemical properties.…”
Section: Introductionmentioning
confidence: 99%